Renewable Energy and Economic Growth: Investigating Their Effects on Carbon Emissions in ASEAN Countries - Nasution, Inggrita Gusti Sari; Hasyim, Sirojuzilam; Soeparno, Wahyu Sugeng Imam; Anggia, Yola; Pangaribuan, Sebastian (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between renewable energy adoption, economic growth, and carbon emissions in ASEAN countries, focusing on the potential for sustainable development. ASEAN, comprising Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam, has seen significant economic growth, resulting in increased energy consumption and higher carbon emissions. The reliance on fossil fuels has raised concerns about environmental sustainability. This research employs a panel data analysis approach, by utilizing data from the period of 1990 to 2020 to explore the effects of renewable energy and economic growth on carbon emissions. The study uses a dynamic heterogeneous panel regression model (Panel ARDL) to capture the long-term and short-term dynamics between the variables. Findings reveal that renewable energy consumption has a positive but non-significant impact on carbon emissions in the long term, contradicting expectations that renewable energy reduces emissions. Economic growth similarly shows a positive but non-significant impact on carbon emissions in the long term. The study’s results align with some previous research while challenging others, highlighting the complex and varied nature of these relationships. The research underscores the need for strategic policy interventions and coordinated efforts to balance economic development with environmental sustainability in the ASEAN region. Future research should focus on optimizing renewable energy policies and assessing the socio-economic benefits of transitioning to a low-carbon economy. The insights provided aim to inform policymakers and stakeholders on strategies for achieving sustainable development while fostering economic growth in one of the world’s most dynamic regions.